AN ANALYSIS OF MAINTENANCE PERFORMANCE SYSTEMS IN THE SOUTH AFRICAN MINING INDUSTRY - Kotze, RLM; Visser, JK (The South African Journal of Industrial Engineering, 2012)
The measurement of performance is an essential part of the management process. The planning function usually defines the goals and objectives for the business enterprise or division of the enterprise. The control function should monitor the performance measures and establish corrective action if actual performance deviates significantly from planned performance. Maintenance performance measurement is therefore essential to ensure that maintenance objectives are achieved, and that maintenance adds value for the company. The objective of this paper is to discuss the findings of a project that investigated aspects of the maintenance performance system of a number of mining companies in South Africa. The findings of a survey indicated that maintenance performance management is not yet used to its full potential in the mining industry.